Durability assessment of basalt fiber polymer as reinforcement to expanded clay concrete in harsh environment. Issue 1 (1st January 2021) - Chiadighikaobi, Paschal Chimeremeze; Ashour Alaraza, Hayder A. A.; Ibeh, Nmecha Udo; Niazmand, Milad Ahmad; Adegoke, Muritala A; Tefera, Bewuket Bekele; Vladimir, Jean Paul
Abstract: Basalt fiber-reinforced polymer composites are receiving considerable attention as they represent a low-cost green source of raw materials. In most cases, fiber-reinforced polymer composites face harsh environments, such as chloride ions in coastal marine environments or cold regions with salt deicing. The resistance of fiber-reinforced polymers subjected to the above environments is critical for the safe design and application of such composites. This research aims to develop a framework to investigate the durability properties of the lightweight expanded clay basalt fiber polymer reinforced concrete exposed to the NaCl environment. The specified quantity of concrete structural elements was cured in its specified curing solution for 28-day curing period before testing. The main effect of micro silica is to enhance concrete strength and durability. Dispersed basalt fibers with 20 mm length and 1.6 percent volume were added to the concrete mixtures. The concrete beams were reinforced with 2∅10 mm rebars as reinforcement while the concrete cylindrical columns were reinforced with dispersed chopped basalt fiber. The results show that addition of dispersed chopped basalt fiber in the concrete caused an increase in the flexural and compressive strength of the concrete structural elements. Micro silica enhanced the concrete strength even when immersed in NaCl solution. Basalt fiber and micro silica fume utilization enhanced the mechanical properties of the concrete.